PENGARUH METODE ROLE PLAYING (BERMAIN PERAN)TERHADAP KETERAMPILAN BERBICARA MATERI TEKS PROSEDUR MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 01 PEKIRINGANALIT - Nada Etika; Asep Ardiyanto; Moh. Aniq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this research is the existence of problems at SD Negeri 01 Pekiringanalit in fourth-grade learning, where students are experiencing difficulties in speaking skills. Based on the results of interviews with the fourth-grade teacher at SD Negeri 01 Pekiringanalit and the analysis of questionnaires given to fourth-grade students, speaking skills among fourth-grade students still face several issues, including: 1) Students use their mother tongue, 2) Students still shy to tell stories, 3) Students tell stories in a disorganized and incomplete manner, 4) Students tell stories in a soft voice, 5) Students are still unable to tell stories without the teacher's help, 6) Students are still unable to tell stories without the help of books, 7) Students cannot understand the stories. Therefore, the researcher strives to provide a solution by choosing a learning method to achieve good learning outcomes, namely by using the role-playing method. The researcher used a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design. The population in the study consists of fourth-grade students from SD Negeri 01 Pekiringanalit, with a sample size of 19 students. The data collection techniques used were tests (pretest and posttest) and documentation. The data analysis techniques used are descriptive and inferential analysis with hypothesis testing using the paired samples t-test with the help of SPSS Statistics 26. The results of this study indicate that the role-playing method can impact Indonesian language learning, and there is a significant difference between learning before the implementation of the role-playing method and after its implementation in the learning process. The significant difference is influenced by the pretest and posttest scores conducted before and after the implementation. The average pretest score was 30.79, while the average posttest score was 70, indicating that the results were higher than the pretest. The results indicate the influence of the role-playing method in Indonesian language learning, as seen from the paired samples t-test with a result of 0.000 < 0.05. Thus, it can be concluded that there is a difference between the pretest and posttest scores, meaning that the role-playing method can impact Indonesian language learning. Keywords: Influence, Role playing method, Indonesian language learning, Grade IV